2005
DOI: 10.1385/ijgc:35:3:171
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Intestinal Trefoil Factor (TFF-3) in Hepatocellular Carcinoma

Abstract: TFF-3 is commonly expressed in HCC and its expression correlates with tumor grade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Our result demonstrated that tumor cells of HCC highly expressed many angiogenic factors, which play a critical role in the angiogenesis of HCC. Several studies reported similar results of angiogenic factors including Ang-2, MT3-MMP [19], MMP-2, MMP-9 [20], Trefoil peptides-3 (TFF-3) [21], Thrombospondin-1 [22], Basic fibroblast growth factor (bFGF) [23]. VEGF plays a critical role in mediating angiogenesis in HCC [1,7].…”
Section: Discussionmentioning
confidence: 84%
“…Our result demonstrated that tumor cells of HCC highly expressed many angiogenic factors, which play a critical role in the angiogenesis of HCC. Several studies reported similar results of angiogenic factors including Ang-2, MT3-MMP [19], MMP-2, MMP-9 [20], Trefoil peptides-3 (TFF-3) [21], Thrombospondin-1 [22], Basic fibroblast growth factor (bFGF) [23]. VEGF plays a critical role in mediating angiogenesis in HCC [1,7].…”
Section: Discussionmentioning
confidence: 84%
“…It is overexpressed in a wide range of human tumors of skin, breast, urogenital, gastrointestinal tract and liver (16)(17)(18)(19)(20)(21)(22)(23) and is thought to induce cancer cell growth. Tff3 overexpression appears to be a frequent event not only in spontaneous (23), transgenicinduced (23), chemically-induced (24) mouse liver tumors, but also in various risk factor-induced human HCC (23).…”
Section: Discussionmentioning
confidence: 99%
“…gastric cancer [18], pancreatic cancer [19], hepatocellular carcinomas [20], colon carcinoma [21] and breast cancer [13,22]. Besides, TFF3 expression correlates with the tumor grade in hepatocellular carcinoma [23] and TFF3 is highly expressed in intestinal metaplasia and a marker for poor prognosis in gastric carcinoma [24]. On the other hand, TFF1-knockout mice develop gastric carcinomas and adenomas [25] and patients with gastric cancer usually display reduced TFF1 levels.…”
Section: Introductionmentioning
confidence: 99%